Ipsilateral Motor Evoked Potentials as a Measure of the Reticulospinal Tract in Age-Related Strength Changes - Maitland, Stuart; Baker, Stuart N. (Frontiers in Aging Neuroscience, 2021)
Background The reticulospinal tract (RST) is essential for balance, posture, and strength, all functions which falter with age. We hypothesised that age-related strength reductions might relate to differential changes in corticospinal and reticulospinal connectivity. Methods We divided 83 participants (age 20-84) into age groups <50 (n=29) and ≥50 (n=54) years; five of which had probable sarcopenia. Transcranial Magnetic Stimulation (TMS) was applied to the left cortex, inducing motor evoked potentials (MEPs) in the biceps muscles bilaterally. Contralateral (right, cMEPs) and ipsilateral (left, iMEPs) MEPs are carried by mainly corticospinal and reticulospinal pathways respectively; the iMEP/cMEP amplitude ratio (ICAR) therefore measured the relative importance of the two descending tracts. Grip strength was measured with a dynamometer and normalised for age and sex. Results We found valid iMEPs in 74 individuals (n=44 aged ≥50, n=29 <50). Younger adults had a significant negative correlation between normalised grip strength and ICAR (r=-0.37, p=0.045); surprisingly, in older adults the correlation was also significant, but positive (r=0.43, p=0.0037). Discussion Older individuals who maintain or strengthen their RST are stronger than their peers. We speculate that reduced RST connectivity could predict those at risk of age-related muscle weakness; interventions that reinforce the RST could be a candidate for treatment or prevention of sarcopenia.